U.S. Undergraduate Education in Public Health: Hot or Not? - Yelena N. Tarasenko; Joel M. Lee (Frontiers Media S.A., 2015)
Objectives. Undergraduate public health education has received growing attention in recent years. This includes a Washington Post article referring to undergraduate public health education as a hot field for a global generation, the Critical Component Elements of an Undergraduate Major in Public Health developed by the Association of School and Programs in Public Health (ASPPH), and a recent report from the de Beaumont Foundation and ASPPH. To evaluate the demand for the degree and assess the current state of undergraduate public health education, the researchers examined the number and characteristics of publicly reported U.S. baccalaureate public health programs. Methods. The researchers reviewed three 2013 college directories and the ASPPH website and identified 112 institutions that used the term public health in their baccalaureate degree listings that guide prospective students in selecting an academic program. The undergraduate degree in public health was defined as a major leading to a B.S., B.A. or other baccalaureate degree in public health or public health studies that provides students with a strong general background in areas of knowledge basic to public health, or a specialized training in at least one of the five core disciplines of public health. The researchers then compared the degree contents as listed in the directories to the institutions' websites to verify offering a public health curriculum. Carnegie Commission on Higher Education's classifications of colleges and universities were applied to assess the characteristics of institutions offering baccalaureate degrees in public health. Results. Only 54 of the 2,968 U.S. institutions of higher education provided online information meeting the definition of an active undergraduate public health degree program. Conclusion. While public health may be a hot field in terms of the interest that it generates, the actual number of verified undergraduate programs available is relatively modest.